KONSTRUKSI GARUK UNTUK KELESTARIAN SUMBERDAYA KERANG - Gondo Puspito (Bumi Lestari Journal of Environment, 2013)
AbstractDredge is known as cockle collector which is not selective to the shell size and its operationdamages the cockle’s resources. The objectives of this research were to obtain better dredgeconstruction which was more productive and selective to the cockle size. The end of theteeth was bent 30o to increase number of the catch. Separator was used to make the dredgebecome more selective for the shell size. In this research, gap between separator grids wasadjusted to economical size of cockle Anadara granosa, which was 40 mm long of shell.Results showed that dredge with 30o bended teeth caught 919 cockles, or 2.18 times morethan standard teeth of dredge (412 cockles). The using of separator made dredge becamemore selective. It only retained cockle Anadara granosa and Anadara antiquata with lengthof shell l e” 39.96 mm and l e” 35.11 mm.